2020 Policy Consultation for the Kurdistan Regional Government I: Improving the Banking and Payment, Taxation System, Tourism Industry, and Industrial Investment - Sohn, Wook; Liu, Cheol; Lee, Jongyearn; Kim, Kye Hwan; Lee, Weonvin (KDI School of Public Policy and Management, 2021)
The “Policy Consultation for the Kurdistan Regional Government I” was carried out as the first round project under the agreement among the Kurdistan Regional Government (KRG), Korea National Oil Corporation and KDI School of Public Policy and Management. The four key consultation agendas were identified as top policy priorities by the KRG: (1) banking and payment, (2) taxation system, (3) tourism development, and (4) industrial investment. Our findings and recommendations for each policy area are summarized in this report.